Nrf2 acts cell-autonomously in endothelium to regulate tip cell formation and vascular branching - Yanhong Wei; Junsong Gong; Rajesh K. Thimmulappa; Beata Kośmider; Shyam Biswal; Elia J. Duh (2013)
Angiogenesis, in which new blood vessels form via endothelial cell (EC) sprouting from existing vessels, is a critical event in embryonic development and multiple disease processes. Many insights have been made into key EC receptors and ligands/growth factors that govern sprouting angiogenesis, but intracellular molecular mechanisms of this process are not well understood. NF-E2-related factor 2 (Nrf2) is a transcription factor well-known for regulating the stress response in multiple pathologic settings, but its role in development is less appreciated. Here, we show that Nrf2 is increased and activated during vascular development. Global deletion of Nrf2 resulted in reduction of vascular density as well as EC sprouting. This was also observed with specific deletion of Nrf2 in ECs, but not with deletion of Nrf2 in the surrounding nonvascular tissue. Nrf2 deletion resulted in increased delta-like ligand 4 (Dll4) expression and Notch activity in ECs. Blockade of Dll4 or Notch signaling restored the vascular phenotype in Nrf2 KOs. Constitutive activation of endothelial Nrf2 enhanced EC sprouting and vascularization by suppression of Dll4/Notch signaling in vivo and in vitro. Nrf2 activation in ECs suppressed Dll4 expression under normoxia and hypoxia and inhibited Dll4-induced Notch signaling. Activation of Nrf2 blocked VEGF induction of VEGFR2-PI3K/Akt and downregulated HIF-2α in ECs, which may serve as important mechanisms for Nrf2 inhibition of Dll4 and Notch signaling. Our data reveal a function for Nrf2 in promoting the angiogenic sprouting phenotype in vascular ECs.